Estudio comparado de la figura de los preacuerdos en Estados Unidos y Colombia (2015)
This paper object is the study of the plea bargains in the American adversarial criminal justice system and Colombian Adversarial System and propose the advantages and disadvantages of using the figure of negotiation. For the development of this, a constant comparison is made in the letter of the use of plea bargains in both countries .For finally; the analysis United States is the federal penal system